Assessment of machining cost for end-milling of Ti-6Al-4V titanium alloy through RSM-based parametric model - Karim, A.N. Mustafizul; Ikram, M; Kays, H. M. Emrul; Abdesselam, M.; Ginta, Turnad Lenggo (Trans Tech Publications, Switzerland, 2014)
Past few decades have been marked by significant achievements in the development of cutting tools and machining processes. End-milling operation with Polycrystalline Diamond (PCD) cutting tool insert presents a good technical solution for machining “difficult-to-cut materials”. However, the cost of each technical or technological solution is a major concern in the decision making process. It is quite common for a solution developer to encounter a question like “How much will this new method cost?” before proceeding for implementation. PCD insert applied as a cutting tool is a recent development and evaluation of economic performance of this cutting tool insert in end-milling of a-difficult-to-cut material such as Ti-6Al-4V titanium alloy can be of significant importance to the manufacturer. However, cost economy depends significantly on the correct choice of cutting conditions especially in the context of cutting parameters. To determine the economically desired levels of the cutting parameters for PCD insert to end-mill Titanium alloy we have presented a RSM-based mathematical model which would help to estimate the cost of removing unit volume of material and to find out the optimum cutting conditions leading to minimum machining cost.